(untitled) (Fiep Bulletin - online, 2014)
The purpose of this study was to identify the intensity of the pain referred by the patients and the professionals’ opinion about the factors of pain risk post-thoracotomy. It a transversal study and quantitative approach. 40 patients submitted to the thoracotomies were researched according to their pain and 13 requested professionals gave their opinions about the intensity of pain from zero to ten in six risk factors for the pain post-thoracotomy: time of surgery, type of surgical incision, drain thoracic, anesthesia type, age and sex. The average of the pain was compared between the professionals and the patients and it was observed that the professionals’ opinion about the surgical time, the location of the thoracic drains and the anesthetic type (they presented p-value of 0,00, 0,00 and 0,01, respectively) they have influence in the submitted patients’ thoracotomy pain, however the pain told by the patients to be compared among the risk factors for pain was not observed its statistics differences. The evaluation of the pain due to thoracotomies by the professionals that followed submitted patients of thoracotomies is essential in the accomplishment of an effective conduct to minimize the post-operative pain, aiding this way, in the procedures of physical therapy.